Emotional intelligence as a cognitive-emotional ability - Andreja Avsec; Sonja Pečjak (Psihološka Obzorja, 2003)
In the article we analyse Mayer and Salovey's model of emotional intelligence. The authors have defined it for the first time in the 90's, delimited its relation to the social intelligence and formed two tests for its measurement, which are unique published tests of their kind. The authors try to separate their approach towards the measurement of emotional intelligence from the self-report measures and from defining emotional intelligence as a set of personality traits. Besides the measurement of emotional intelligence with the tests of maximum performance, authors try to prove that correlation between emotional abilities indicate similar hierarchical structure as is characteristic for other kinds of intelligence. Since the first test for measuring the emotional intelligence was published in 1997 and there have been no other published tests of this kind yet, it is very difficult to evaluate its metric characteristics and the validity of the model. Anyhow, in defining and measuring the emotional intelligence researchers face similar problems as in social intelligence research.